Aqueous and organic inks of carbon xerogels as models for studying the role of porosity in lithium-ion battery electrodes. (5th November 2016) - Rey-Raap, Natalia; Piedboeuf, Marie-Laure C.; Arenillas, Ana; Menéndez, J. Angel; Léonard, Alexandre F.; Job, Nathalie
Abstract: The electrochemical performances of lithium-ion batteries depend to a great extent on the method used to prepare the electrodes and on the pore texture of the active material. In the present study, carbon xerogels with different pore sizes and pore volumes were synthesized by means of microwave heating. These carbonaceous materials were used to prepare lithium-ion battery anodes. Generally, electrodes are prepared by coating a slurry made of an active material, a binder and N -methyl-2-pyrrolidone as organic solvent. The disadvantage of this solvent is that it is both toxic and costly. In this work, the use of water instead of the organic solvent and water-soluble binders yielded electrodes with similar electrochemical performances making the battery assembly process more economic and environmentally friendly. The results of this study also confirm that the use of an aqueous preparation pathway does not undermine the interdependence between the electrochemical properties of the cells and the porous properties of the carbon xerogels. Graphical abstract: Highlights: Tailored carbon xerogels by microwave heating in a fast and cheap synthesis process Substitution of the usual organic solvent in preparing electrodes for batteries Carbon xerogels as models to evaluate the role of porosity in the electrochemistry